2015
DOI: 10.1159/000439431
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib and Tivantinib, but Not INC280, Induce Antiproliferative and Antimigratory Effects in Human Neuroendocrine Tumor Cells in vitro: Evidence for ‘Off-Target' Effects Not Mediated by c-Met Inhibition

Abstract: Background/Aims: The hepatocyte growth factor/transmembrane tyrosine kinase receptor c-Met has been defined as a potential target in antitumoral treatment of various carcinomas. We aimed to investigate the direct effect of c-Met inhibition on neuroendocrine tumor cells in vitro. Methods: The effects of the multi-tyrosine kinase inhibitors cabozantinib and tivantinib and of the highly specific c-Met inhibitor INC280 were investigated in human pancreatic neuroendocrine BON1, bronchopulmonary NCI-H727 and midgut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
(127 reference statements)
1
14
0
Order By: Relevance
“…Initially, tivantinib was identified as an MET inhibitor in a kinase assay (5), but subsequent work showed that it was able to bind only to the inactive unphosphorylated-MET and has no direct effect on the MET kinase activity (26). Next, several studies (5,(27)(28)(29)(30), performed in cellulo, have shown a decreased phosphorylation of MET after a long-time exposure (24 hours) to tivantinib contrasting with our results and others that were obtained with a short-time (4-6 hours) exposure in hepatocellular or other types of tumor cells (11)(12)(13). Indeed, after 24 hours of tivantinib exposure, a decrease in both phospho-and total MET proteins was shown by Western blot analysis in most of the cell models (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, tivantinib was identified as an MET inhibitor in a kinase assay (5), but subsequent work showed that it was able to bind only to the inactive unphosphorylated-MET and has no direct effect on the MET kinase activity (26). Next, several studies (5,(27)(28)(29)(30), performed in cellulo, have shown a decreased phosphorylation of MET after a long-time exposure (24 hours) to tivantinib contrasting with our results and others that were obtained with a short-time (4-6 hours) exposure in hepatocellular or other types of tumor cells (11)(12)(13). Indeed, after 24 hours of tivantinib exposure, a decrease in both phospho-and total MET proteins was shown by Western blot analysis in most of the cell models (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Then medium was replaced by fresh medium and cells were incubated with different concentrations of TH588 (5 μM and 10 μM), either alone or in combination with 5-FU (5 μM) or everolimus (10 nM). The incubation times were up to 96 h. Western blotting was conducted as described previously [23]. The following primary antibodies used were: pAKT (Ser473) (#4060), AKT (#2920), pERK1/2 (Thr202/Tyr204) (#4370), p4EBP1 (Ser65) (#9451), 4EBP1 (#9644), pRb (Ser780) (#9307), pCDK1 (Tyr15) (#4539), CDK1 (#9116), Cyclin B1 (#12231), Cyclin D1 (# 2926), Cyclin D3 (#2936), CDK4 (#12790), CDK6 (#13331), Chk1 (#2360), pChk2 (Ser19) (#2666), pChk2 (Thr68) (#6334), Chk2 (#6334), Parp (#9542), PCNA (#2586) (all from CellSignaling, Danvers, USA), p16 INK4A (ab151303) (abcam, Cambridge, UK), Rb (#614602) (Biolegend, San Diego, USA), Actin (A5441) (Sigma, St.Louis, USA), ERK1/2 (06–182) (Merck-Millipore, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Its kinase-inhibiting profile was reported to affect in vitro proliferation and migration of human NEN cell lines (pancreatic BON1, bronchopulmonary NCI-H727 and midgut GOT1 cells), causing arrest in the G2 phase of cell cycle (Reuther et al 2016). In vivo, using RIP1-Tag2 transgenic mice, cabozantinib reduced not only pancreatic tumor burden but also invasion and metastasis, an effect related to the simultaneous inhibition of c-MET and VEGF signaling (Sennino et al 2012).…”
Section: Other New Mtkismentioning
confidence: 99%